PENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP RAHMAT ISLAMIYAH MEDAN - Setiawan, Hasrian Rudi; Masitah, Widya; Abrianto, Danny (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
The purpose of this study was to improve student activity and learning outcomes at SMP Rahmat Islamiyah Medan. In addition, this study aims to determine student responses to Islamic religious education subjects when the Team Assisted Individualization (TAI) Learning Model is applied. This type of research is classroom action research, while the method used in this study is to conduct learning and observation in class using a repetitive cycle, the cycle will be stopped until the activity and student learning outcomes increase according to the target set by the researcher. The procedure of implementation through four stages, namely: planning,implementation, observation, and reflection. The instruments used for data collection in this study were achievement tests, observations, questionnaires and documentation. The data analysis technique is using descriptive. The results of the research that is produced in the first cycle produced that student learning activities have increased compared to the pre-action stage, namely in the first cycle student learning activities have reached 82.20%. While student learning outcomes have increased compared to the pre-action stage, namely in the first cycle there are 29 people who get a complete score, amounting to 87.88% and only 3 students who have not completed, amounting to 15.12%. Whereas students' responses to Islamic religious education subjects when using the Team Assisted Individualization (TAI) Learning model, showed a very positive response.